Waste Anesthetic Gase: A Forgotten Problems - Andi Miarta; Mayang Indah Lestari; Zulkifli (Journal of Anesthesiology and Clinical Research, 2020)
Waste anesthetic gas (WAG) is a small amount of inhaled anesthetic gas that comes out of the patient’s anesthesia breathing circuit into the envorinment air while the patient is under anesthesia. According to American Occupation Safety and HealthAdministration (OSHA) more than 200.000 healthcare workers especially aneaesthesiologist, surgery nurse, obstetrician and surgeons are at risk of developing work-related disease due to chronic exposure to WAG. Exposure to WAG in short time associated with multiple problems such as headaches, irritability, fatigue, nausea, drowsiness, decrease work efficiency and difficulty with judgment and coordination. While chronic exposure of WAG is associated with genotoxicity, mutagenicity, oxidative stress, fatigue, headache, irritability, nausea, nephrotoxic, neurotoxic, hepatotoxic, immunosuppressive and reproductive toxicological effect. Waste anesthetic gases are known as environmental pollutants and will be released from the OR to the outside environment then the substance will reach the atmosphere damaging ozone layer. Exposure to trace WAG in the perioperative environment cannot be eliminated completely,but it can be controlled. Controlling WAG can be achieve by using scavenging system, proper ventilation, airway management, ideal anesthetic choice, maintaining anesthesia machine and equipment, hospital regulation and routine healthcare workers health status examination.